Pemilihan destinasi kuliner melalui TikTok bagi Generasi Z di Indonesia: Model UTAUT2 - Klarissa, Kezia; Josephine, Abigail; Kristanti, Monika (Universitas Tarumanagara, 2024)
This study adopted the UTAUT2 model to examine the influence of TikTok on behavioral intentions and the actual behavior of generation Z in Indonesia in choosing culinary destinations. In this research, behavioral intention has the mediation role between the use of TikTok and actual behavior. This model used 6 variables from UTAUT2: performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, and habit; and added 1 variable from the extended model of UTAUT2: perceived trust. This descriptive study involves quantitative data using a questionnaire as a data collection method. The method of sampling is judgmental where the respondents are generation Z aged 18 to 25 years old that have TikTok accounts and are active users of TikTok. The researcher distributed questionnaires to 398 respondents online and onsite at some universities and café in Surabaya, and the data was processed using SmartPLS 4. The results found that performance expectancy, social influence, habit, and perceived trust positively significantly affect behavioral intention; habit and behavioral intention positively significantly affect the actual behavior of generation Z to use TikTok in choosing culinary destinations. These findings can be a guide for culinary business owners to increase the use of the TikTok platform as a marketing strategy. Penelitian ini mengadopsi model UTAUT2 untuk meneliti pengaruh penggunaan TikTok terhadap behavioral intention dan actual behavior generasi Z di Indonesia dalam memilih destinasi kuliner. Adapun behavioral intention berperan sebagai variabel mediasi. Model ini menggunakan 6 variabel dari UTAUT2, yaitu performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, habit, dan menambahkan 1 variabel dari extended model of UTAUT2: perceived trust. Jenis penelitian adalah kuantitatif. Peneliti menggunakan judgmental sampling, yaitu generasi Z yang berusia 18-25 tahun yang mempunyai akun TikTok dan merupakan pengguna aktif TikTok. Peneliti menyebarkan kuesioner kepada 398 responden baik secara online maupun onsite di lingkungan kampus dan kafe, kemudian data diolah menggunakan software SmartPLS 4. Hasil ditemukan bahwa variabel perceived trust, habit, social influence, dan performance expectancy secara positif signifikan memengaruhi behavioral intention; habit dan behavioral intention secara positif signifikan memengaruhi actual behavior generasi Z untuk menggunakan TikTok dalam memilih destinasi kuliner. Temuan ini dapat menjadi panduan bagi pemilik usaha kuliner untuk meningkatkan penggunaan platform TikTok sebagai strategi pemasaran.